Distance learning in the digital era - Epriyanti, Epriyanti; Ahyani, Nur; Kusumawati, Nila (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
The Covid 19 pandemic makes the learning process must be done remotely. The learning process, which is usually done face-to-face, changes to a distance. There are many new things in distance learning. Adaptations are carried out by teachers and students. Increased mastery of technology is carried out. This research uses the library research method, where this research in collecting information and data uses a variety of materials and materials in the library, namely in the form of books, journals, documents, magazines, historical stories, news, and other relevant sources. Distance learning requires adequate facilities and infrastructure, such as laptops, computers, smartphones and internet networks. This becomes one of the challenges of distance learning. Distance learning makes students more independent, because it places more emphasis on being student centered. They are more courageous to express their opinions and ideas. As well as the government has also provided several platforms that students can use to learn.